DISTRIBUSI UNGGAS DARI PASAR PALAPA DAN PASAR SELASA KOTA PEKANBARU SEBAGAI JALUR POTENSIAL PENYEBARAN VIRUS AVIAN INFLUENZA - Jully Handoko; Rahmi Febriyanti (Jurnal Peternakan, 2011)
The research was conducted in August 2010 to October 2010 in Pekanbaru. Location of the research was focused attraditional markets included Palapa and Selasa market. This study aimed to determine the distribution patterns of birds thatare traded in traditional markets in order to describe the potential ways of the spread of Avian Influenza virus. This studyused survey methods, involved the poultry traders and buyers as the respondents of both markets. The poultry buyers weretaken by randomly and purposively. Interview to buyers poultry were conducted 1 time a week for 4 weeks. The variablesincluded 1) type of poultry sold, 2) area of origin of poultry for sale; 3) the number of poultry sold; 4) domicile poultry buyer,and 5) the need for buying poultry. Based on the results of the study and description of the discussion could be drawn someconclusions, as follow 1) the pattern of distribution of live poultry were traded at Palapa and Selasa market covered a range of Pekanbaru City area, outside the city of Pekanbaru and outside the Riau Province; 2) distribution of live poultry caused by the mobilization of traders and buyers of poultry has the potential for transmission, distribution and outbreaks of avian influenza, both among the animals (poultry) or to humans.